Intermediation behavior of the financial superstructure in response to environmental stimuli: theory, issues and further empirical evidence from nigeria - Ezirim, Chinedu B; Muoghalu, Michael I; Emenyonu, Emmanuel (Journal of African Business, 2007)
This paper is an empirical extension aimed at investigating the relationships between the indicators of the financial superstructure and its intermediation environments; and especially how the former responds to the effects of the latter. Intermediation-environmental models patterned after multivariate regression, causality, and partial adjustment models of both linear and log-linear formulations were estimated and analyzed. The results reveal that three environments: socio-political, regulatory, and international finance-exerted significant effects on the intermediation function of the superstructure. Previous intermediation successes ginger up current performance. In the long run, the effects of the environmental factors on the intermediation function of the superstructure, in whatever direction, more than quadruples. In any given year, the Nigerian financial superstructure attains only about 21.9% of desired (optimal) FIR. Given this, it would take about 4-1/2 years for it to adjust its intermediation operations (FIR), in light of the effects of environmental factors, to optimal levels in order to significantly impact the economy as desired. Some consistent behavioral traits were identified from the results to include: the precepts of potential maximization, profit maximization, accommodation principles, survival and cost-minimization principles, and the neutrality axiom. © 2007 by The Haworth Press, Inc. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-551-138-999-026 tex.type: [object Object]
Keywords: Africa; Eco-financial environments; Environmental Stimuli; Financial Superstructure; Intermediation Behavior; International financial environments; Nigeria; Regulatory environments; Socio-political environments; Sub-Saharan Africa; West Africa; Zingiber officinale; behavioral response; dept.acc; economic structure; empirical analysis; finance; modeling; regression analysis; socioeconomic impact; theoretical study